Bispecific antibodies in indolent B-cell lymphomas - Radhakrishnan, Vivek S.; Davies, Andrew J. (Frontiers in Immunology, 2024)
The advent of immunotherapy in lymphomas, beginning with Rituximab, have led to paradigm shifting treatments that are increasingly bringing a greater number of affected patients within the ambit of durable disease control and cure. Bispecific antibodies harness the properties of the immunoglobulin antibody structure to design molecules which, apart from engaging with the target tumour associated antigen, engage the host's T-cells to cause tumour cell death. Mosunetuzumab, an anti-CD20 directed bispecific antibody was the first to be approved in follicular lymphoma, this has now been followed by quick approvals of Glofitamab and Epcoritamab in diffuse large B-cell lymphomas. This article reviews contemporary data and ongoing studies evaluating the role of bispecific antibodies in indolent b-cell non Hodgkin lymphomas. This is an area of active research and presents many opportunities in advancing the treatment of indolent lymphomas and potentially forge a chemo-free treatment paradigm in this condition.